A verbatim film-research collaboration seeking to raise awareness of prison suicide, 2020-2024 - Tomczak, Philippa (UK Data Service, 2024)
This is qualitative data collection of semi-structured interviews conducted between June-July 2023, and online surveys conducted throughout 2022, within a study that examined how the Prisons and Probation Ombudsman (seek to) effect change in prisons following prisoner suicides and how verbatim film can help to increase the impact of research findings. The study ran from 2021-2023. Prisoner suicide rates are consistently higher than rates among communities living outside. Between 2012 and 2016, England and Wales’s prison suicide rates more than doubled, hitting record numbers in 2016. Often those most invested in prison safety are those personally impacted, and campaigns by prisoners’ families can have material effects. This project included a collaboration between an academic research team, a bereaved parent and a theatre company, which aimed to raise awareness of prison suicide through verbatim film and communicate key messages to stakeholders across criminal justice. In May 2019, Dutch courts refused to deport an English suspected drug smuggler, citing the potential for inhuman and degrading treatment at HMP Liverpool. This well publicised judgment illustrates the necessity of my FLF: reconceptualising prison regulation, for safer societies. It seeks to save lives and money, and reduce criminal reoffending. Over 10.74 million people are imprisoned globally. The growing transnational significance of detention regulation was signalled by the Optional Protocol to the United Nations Convention against Torture/OPCAT. Its 89 signatories, including the UK, must regularly examine treatment and conditions. The quality of prison life affects criminal reoffending rates, so the consequences of unsafe prisons are absorbed by our societies. Prison regulation is more urgent than ever. England and Wales' prisons are now less safe than at any point in recorded history, containing almost 83,000 prisoners: virtually all of whom will be released at some point. In 2016, record prison suicides harmed prisoners, staff and bereaved families, draining 385 million punds from public funds. Record prisoner self-harm was seen in 2017, then again in 2018. Criminal reoffending costs £15 billion annually. Deteriorating prison safety poses a major moral, social, economic and public health threat, attracting growing recognition. Reconceptualising prison regulation is a difficult multidisciplinary challenge. Regulation includes any activity seeking to steer events in prisons. Effective prison regulation demands academic innovation and sustained collaboration and implementation with practitioners from different sectors (e.g. public, voluntary), regulators, policymakers, and prisoners: from local to (trans)national levels. Citizen participation has become central to realising more democratic, sustainable public services but is not well integrated across theory-policy-practice. I will coproduce prison regulation with partners, including the Prisons and Probation Ombudsman, voluntary organisations Safe Ground and the Prison Reform Trust, and (former) prisoners. This FLF examines three diverse case study countries: England and Wales, Brazil and Canada, developing multinational implications. This approach is ambitious and risky, but critical for challenging commonsensical beliefs. Interviews, focus groups, observation and creative methodologies will be used. There are three aims, to: i) theorise the (potential) participatory roles of prisoners and the voluntary sector in prison regulation ii) appraise the (normative) relationships between multisectoral regulators (e.g. public, voluntary) from local to (trans)national scales iii) co-produce (with multisectoral regulators), pilot, document and disseminate models of participatory, effective and efficient prison regulation in England and Wales (and beyond) - integrating multisectoral, multiscalar penal overseers and prisoners into regulatory theory and practice. This is an innovative study. Punishment scholars have paid limited attention to regulation. Participatory networks of (former) prisoners are a relatively new formation but rapidly growing in influence. Nobody has yet considered agencies like the Prisons Inspectorate and Ombudsman alongside voluntary sector organisations and participatory networks, nor their collective influences from local to transnational scales. Nobody has tried to work with all of these agencies to reconceptualise prison regulation and test it in practice. Findings will be developed, disseminated and implemented internationally. The research team will present findings and engage with diverse stakeholders and decision makers through interactive workshops (Parliament, London, Manchester, Liverpool and Birmingham), and multimedia outputs (e.g. infographics). This FLF has implications for prisons and detention globally, and broader relevance as a case study of participatory regulation of public services and policy translation.